2019
DOI: 10.13005/bpj/1833
|View full text |Cite
|
Sign up to set email alerts
|

FTIR and Elementary Analysis of Trigona Honey, Apis Honey and Adulterated Honey Mixtures

Abstract: Honey is at high risk for the adulteration in global trade. Studies on the authenticity of stingless bee honey from Trigona spp. is necessary since the market demand for this product is increasing, particularly in Malaysia, due to its high nutritional value. FTIR spectroscopy has recently been used approach for a rapid and non-destructive measurement of honey quality and discriminate adulterated honey. The purpose of this study is to determine the FTIR and elementary content of Trigona spp. and Apis spp. honey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…Based on the local beekeepers’ report, the adulteration of SBH involves dilution with water to increase the yield volume of the honey to fraudulently increase income. In addition, in certain cases, cheaper honey is blended with a sour-tasting liquid such as vinegar to create a sour taste that resembles that of SBH, and then market it at a high price commensurate with the authentic SBH [ 16 ]. However, due to the complexity of food matrices, most standard approaches can only detect a small number of adulterants in stingless bee honey without a thorough examination of all of its attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the local beekeepers’ report, the adulteration of SBH involves dilution with water to increase the yield volume of the honey to fraudulently increase income. In addition, in certain cases, cheaper honey is blended with a sour-tasting liquid such as vinegar to create a sour taste that resembles that of SBH, and then market it at a high price commensurate with the authentic SBH [ 16 ]. However, due to the complexity of food matrices, most standard approaches can only detect a small number of adulterants in stingless bee honey without a thorough examination of all of its attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the functional group of formulations A1, A2, A3 and the control sample, SBH, after being subjected to HPH for 5 cycles at 100 MPa at room temperature, was still the same as the functional group of the honey. Besides, it has been reported by Mail et al [ 42 ] that the functional groups of SBH are almost identical to those of common honey produced by Apis bees. The authors also stated that SBH has lower absorption in carbohydrate regions and high absorption in water regions due to its natural chemical constituents.…”
Section: Resultsmentioning
confidence: 74%
“…A study by Mail et al [ 96 ] suggested that Trigona spp. honey can be clearly distinguished from Apis spp.…”
Section: Authentication Of Honey Using Ir Spectroscopymentioning
confidence: 99%
“…Reprinted with permission from ref. [ 96 ]. Copyright 2019 Copyright Oriental Scientific Publishing Company.…”
Section: Figurementioning
confidence: 99%